Instruments for the evaluation of adherence to treatment used in JABA articles (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Different instruments have been developed to evaluate adherence to treatment behaviors. Observation is the main procedure used by behavior analysts, whose challenge is to find conditions for conducting observations in health. The purpose of the study is to analyze the instruments used by behavior analysts to evaluate adherence behaviors. A systematic review of articles published in JABA was conducted, describing studies that carried out interventions to increase adherence. Twenty-six articles were selected and fully read. Observation was the most used procedure to evaluate patient's adherence, followed by biological measurement and electronic monitors. The researches did not evaluate antecedent and consequent stimuli to the responses of interest. It is recommended that the observation procedure is used in such a way that enables the identification and evaluation of variables that allow a functional analysis of the behaviors of interest, permitting their real comprehension, prediction and control.
Keywords: Adherence do treatment; Instrument; Evaluation; Behavior Anlysis; Health